Role of 4-methylimidazole in liver toxicity: A histomorphometric study in albino rats - Suman Yadav; Sunita Kalra; Surbhi Wadhwa; Pooja Rani (Wolters Kluwer Medknow Publications, 2022)
Background: These days, food products industry involves the commercial production and addition of food colors, which comprises many food dyes, including caramel colors. 4-methylimidazole (4-MEI) is a component of various caramel-colored food products such as bakery, beer, soft drinks, coffee and sauces, which are consumed daily. The most common route of exposure is ingestion and liver is the organ of detoxification. The histomorphometric observations in liver after 4-MEI consumption have not been reported to the best of our knowledge and so the present study have been designed to evaluate the same. Methodology: Adult male Wistar albino rats weighing 150-200 g were procured for the study and divided into the control and experimental groups. The experimental animals were given 4-MEI orally by gavage tube at a dose of 250 mg/kg body weight daily for 1 month, while the control animals received distilled water. At the end of experiment, all the animals were euthanized under ether anesthesia by perfusion with Formal saline. Dissection and histopathological processing of liver was done for the examination. Results: The histomorphometric observations of the liver in experimental rats revealed a significant increase in sinusoidal width indicative of sinusoidal dilatation and congestion. There was a significant increase in the size of hepatocytes while a decrease in the size of their nuclei was noted, suggestive of ballooning degeneration. Conclusion: The findings in the present study strongly suggest hepatocellular damage caused by ingestion of 4-MEI found in caramel color dyes used routinely in the food industry.